Bussiness development strategy in coffee shop (study on Berawal Coffee & Dimsum in Bagusrangin disrict, Bandung city) - Puspita, Putri Aina; Wijaya, Fanji (Junal Ilmu Manajemen, 2024)
The purpose of this research is to build an innovation strategy focused on commercial development for Berawal Coffee & Dimsum through the creation of opportunity-generating tactics. In this research, a case study was used along with a qualitative approach. The owner and management team of Berawal Coffee, who play an important role as key informants and are directly involved in the company's operations or part of the core management, are considered to have the best understanding of the business situation there. The researcher conducted interviews with these people. The researcher used the IFE, EFE, and QSPM matrices to find a number of opportunities, threats, strengths, and weaknesses that became important elements in business development when creating a business plan for Berawal Coffee & Dimsum. Berawal Coffee's evaluation of the Internal and External (IE) Matrix shows that Berawal Coffee is in cell V position. To prevent a decline in sales and loss of profits, the next stage is product development. Berawal Coffee & Dimsum can expand its facilities and geographical reach while maximizing the use of technology for marketing purposes. This could be the first step to growing the company if the strategy is well formulated